Roles of Japanese scripts in Western fashion: Fusion and New Orientalism - Kawabata, Takako (2023)
This paper examines the use of Japanese scripts on fashion items. The use of English on fashion items (e.g. t-shirts) has been observed across the globe and examined in the field of sociolinguistics. In recent years, fashion brands such as Gucci, Coach, Adidas, and Nike have printed Japanese scripts on their clothes alongside their original brand names. A UK fashion brand, Superdry, employ Japanese in their brand name and logos. However, the use of languages other than English has not yet been analysed in the fields of sociolinguistics or fashion. The adoption of different cultural norms is often discussed as a form of cultural appropriation. This paper challenges that view by comparing the use of English and Japanese as well as by discussing possible explanations and the roles of Japanese scripts in fashion. It emerges that Japanese scripts are used due to the symbolic, cultural, and linguistic capital that they hold, as well as with a view to enabling brands to express uniqueness. The paper argues that printing Japanese scripts on fashion items is not a simple representation of Japonisme, but rather a form of cultural and linguistic appreciation. It also asserts that the New Orientalism that has been observed in the adaptation of Japanese scripts to fashion has no connotation of otherness. Instead, it represents an active acceptance of the East and the generation of new cultures. Transcultural flows are observed in the field of fashion in the era of globalisation. This paper presents a new perspective on studies on Orientalism and the use of languages and scripts.